Flip flop! a sticker book - Rau, Dana Meachen 1971-; Christy, Jana (New York Random House, 2011)
Rhyming text explores the many options that summer presents to two best friends, from swimming in a pool versus swimming in the sea, to wearing flip flops versus going barefoot
"2 sticker sheets inside!"--P. [1] of cover
2 13
Keywords: Choice -- Fiction; Stories in rhyme; Summer -- Fiction